The effect of substitution of diaminopimelic acid by 4-hydroxy-diaminopimelic acid on the synthesis and degradation of murein in Escherichia coli 173-25 - Chaloupka, J; Strnadová, M; Vereś, K; Zalabák, V (Folia microbiologica, 1976)
Defects in the formation of the septum and gradually autolysis of cells occur when the dap-dependent mutant of Escherichia coli is grown in a medium with 4-hydroxy-diaminopimelic acid. When the culture grown in the presence of the labelled analogue is supplemented with the non-radioactive diaminopimelic acid a portion of the TCA-soluble radioactivity is released from the cells during 20 min after the addition of diaminopimelic acid. During this time interval the elongated forms formed in the presence of the analogue divide, however, only on the condition that the above forms are not irreversibly damaged. The increased concentration of the analogue in the medium substantially suppresses the irregularities in the development of the septum as well as the degradation of analogue containing cell wall. However, the growth rate in the presence of the analogue is always slightly lower than that in the presence of diaminopimelic acid. The cell wall pulse-labelled with diaminopimelic acid or its analogue for a time interval shorter than 1/4 of the generation time exhibits the same or only slightly higher rate of diaminopimelic acid is probably utilized less effectively for the synthesis of murein than diaminopimelic acid. However, its incorporation into the wall does not result in pronounced damage of the cell.
Keywords: Hydroxy Acids; Cell Division; hydroxykyseliny; kyselina diaminopimelová; Diaminopimelic Acid; kyseliny pimelové; buněčná stěna; mutace; buněčné dělení; Cell Wall; Peptidoglycan; peptidoglykan; Escherichia coli; Pimelic Acids; Mutation